Analisis Isi Sosok Iblis dan Sebuah Ketaatan Dalam Film The Nun - Arfian Suryasuciramdhan; Galang Ramadhan; Dhiyandra Prasetya Gusti; Hocky Nis Kharisma Dewi; Gisella Aisyah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Nun is technically a prequel to the ever-expanding Conjuring Universe. This film tells the story of the origins of VALAK, the super scary demon nun from The Conjuring 2. Synopsis The Nun is set in 1952, at the Carta Monastery in Romania which is known to be haunted and cursed by local residents. This film tells the story of the investigation carried out by Father Burke, Sister Irene and Frenchie into the suicide of one of the nuns in the convent. In their investigation they find out that something is wrong with the place and they have to solve the puzzles one by one. In film this involves the collection and analysis of non-numerical data, such as text, images, or audio recordings. Researchers can use this method to explore the researcher's experience of watching the film, our perceptions of the characters and themes, and the impact of the film on moral beliefs and values. Unlike in the film The NUN, Valak in Christian demonology is actually a demon in the form of a small angel who rides a two-headed dragon, and is considered the commander of 38 legions of evil spirits. Some life lessons that can be taken from this film are obeying God, obeying his commands and staying away from his prohibitions.